Online Teaching of Passive Voice in an Indonesian Vocational School Amid Covid-19: Insights from a Novice English Teacher - Dewi, Senny Rizkya; Mulyani, Euis Rina (PROJECT (Professional Journal of English Education), 2026)
The shift to online learning during the COVID-19 pandemic required English teachers to adopt digital media capable of sustaining instructional effectiveness and student engagement. This study investigated how a novice English teacher utilized videos in teaching students to write passive voice sentences in an online vocational school classroom and examined students’ responses to its implementation. A qualitative descriptive design was employed, involving one English teacher and 20 twelfth-grade vocational students. Data were collected through online-classroom observation, questionnaires, and interviews, and subsequently analyzed qualitatively. The findings reveal that the novice teacher successfully implemented video-assisted instruction to support structured grammar teaching in the online classroom. By integrating multimedia with guiding questions, the ability to replay instructional videos, and continuous corrective feedback, the teacher enhanced students’ conceptual understanding of passive voice and encouraged active participation while facilitating self-paced learning. Moreover, students perceived the video as engaging and helpful. However, some experienced difficulties due to a limited vocabulary. This suggests that multimedia resources should be complemented with appropriate scaffolding to optimize learning outcomes. Thus, while video can foster more adaptive and engaging learning environments, effective teacher facilitation remains essential for successful online language learning.